Usefulness of non-contrast MR imaging in distinguishing pancreatic ductal adenocarcinoma from focal pancreatitis - Lee, Jeong Hyun; Min, Ji Hye; Kim, Young Kon; Cha, Dong Ik; Lee, Jisun; Park, Hyun Jeong; Ahn, Soohyun (Clinical Imaging, 2019)
Background: Accurate differentiation between pancreatic adenocarcinoma and focal pancreatitis is challenging. Purpose: To investigate the usefulness of non-contrast MRI by comparing with multidetector row CT (MDCT) and gadoxetic acid-enhanced MRI in the discrimination of pancreatic ductal adenocarcinoma (PDAC) and focal pancreatitis (FP). Materials and methods: This retrospective study included 187 patients (116 with PDACs and 71 with FP) who underwent gadoxetic acid-MRI and MDCT prior to surgical resection or biopsy. The MRI features of PDAC and FP were compared by two radiologists. Then, two observers independently reviewed the three imaging sets: MDCT, non-contrast MRI (T1-, T2-weighted, and diffusion-weighted images), and MRI with and without gadoxetic acid to determine the diagnostic performances of each imaging modality in the discrimination of PDAC and FP. Results: The significant features on non-contrast MRI for diagnosis of PDAC included peritumoral cyst, pancreatic duct cut-off, clear hypointensity on T1WI, and bile duct dilatation (P < 0.05). Presence of peritumoural cyst showed the highest odds ratio for predicting PDAC. Non-contrast MRI was superior to MDCT in differentiating PDAC from FP with regard to accuracy (84.5% vs 95.5% for observer 1; 85.8% vs. 96.0% for observer 2), sensitivity (83.6% vs. 98.3%; 84.5% vs 97.8%), and negative predictive value (76.3% vs. 97.0%; 77.6% vs 96.4%) (P < 0.05). We found similar diagnostic values between the non-contrast MRI and MRI with and without contrast (P > 0.05) for both observers. Conclusion: Non-contrast MRI is better than MDCT and comparable to MRI with and without gadoxetic acid in differentiating PDAC from FP.
Keywords: Diagnostic performance; Diffusion weighted images; Ductal adenocarcinomas; Focal pancreatitis; MDCT; MR imaging; Negative predictive value; Pancreatic adenocarcinoma; Adult; Aged; Biopsy; Carcinoma, Pancreatic Ductal; Contrast Media; Diagnosis, Differential; Diffusion Magnetic Resonance Imaging; Female; Gadolinium DTPA; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Multidetector Computed Tomography; Pancreatic Ducts; Pancreatic Neoplasms; Pancreatitis; Radiologists; Retrospective Studies; Sensitivity and Specificity; Focal pancreatitis; Gadoxetic acid; MDCT; MR imaging; Pancreatic ductal adenocarcinoma